Gestão da tramitação processual nas varas trabalhistas - Fioreze, Ricardo (2009)
This work analyzes the management of the development of the judicial processes before Labor Courts as an instrument capable of assisting in achieving the effectiveness of the jurisdictional activity and the reasonable duration of the process. The objective is to show how the management fits in the attributions inherent to the function of a judge and the necessity of its adoption in the conduct of the process development. It also identifies moments and acts of the process development when the adoption of management techniques can produce better results and suggest practices that lead to optimizing the available resources and procedural legislation, and to maximizing and, whenever possible, suppressing acts, and to eliminating 'dead stages'. In order to reach such purposes, fundamental theoretical aspects related to the management of organizations and, specifically, to the juridical management at Labor Courts are firstly approached. Secondly, the possibility of managing the (judicial) process itself is stated, aiming at increasing the usefulness of its result, emphasizing the repercussions that this idea causes on the duties inherent to a judge. At last, the proposals of practical application of process management at Labor Courts are expounded, comprising several moments and acts of the process development and its corresponding control.